A novel synthesis of anti-cancer drug gefitinib from 6,7-dimethoxy-3H-quinazolin-4-one - Santoso, Prio; Danova, Ade; Hermawati, Elvira; Natalia, Dessy; Alni, Anita (Penerbit Universiti Kebangsaan Malaysia, 2025)
A novel synthesis of the anticancer drug gefitinib (Iressa) through novel alternative pathway has been successfully carried out. The synthesis was performed using 6,7-dimethoxy-3H-quinazolin-4-one as the starting material through four reaction stages: Chlorination, nucleophilic aromatic substitution, demethylation, and Williamson etherification to produce gefitinib. The chlorination of 6,7-dimethoxy-3H-quinazolin-4-one as the first key step in this synthesis followed by aromatic substitution were effective to produce the target product with high yield (98% for two steps). In addition, synthesis of gefitinib from this precursor omits the necessity for functional group protection and deprotection. Purification was carried out using crystallization and radial chromatography. The structural analysis of the resulting compound was performed using FTIR, 1H-NMR, 13C-NMR, and mass spectrometry. The purity of the resulting compounds was measured using HPLC and melting point measurements (195-197 °C). The overall yield obtained through this pathway was 21%.